The Political Worlds of Women. - Richardson, Sarah (Routledge research in gender and history., 2013)
Traditional analyses of nineteenth-century politics have assigned women a peripheral role. By adopting a broader interpretation of political participation, the author identifies how middle-class women were able to contribute to political affairs in the nineteenth century. Examining the contribution that women made to British political life in the period 1800-1870 stimulates debates about gender and politics, the nature of authority and the definition of political culture. This volume examines female engagement in both traditional and unconventional political arenas, including f.